1997
DOI: 10.1046/j.1469-7580.1997.19140517.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal villosity and microvasculature of the bovine placentome in the second half of gestation

Abstract: The architecture of the fetal villous tree and its vasculature in the bovine placentome were studied in the second half of gestation using both conventional histology and histology of ink-filled blood vessels. These were compared with corrosion casts of plastic fillings of the vasculature, prepared for scanning electron microscopy. This combination of morphological methods allows perception of the villous tree throughout gestation from broad-conical to tall-conical form where branch ramification occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 15 publications
3
43
0
6
Order By: Relevance
“…Fetal villi of cattle, measured at the centre of pedunculated placentomes, were up to four times wider than in the African buffalo whereas the width of villous tips was similar in both genera. Villous trees in cattle therefore adopt a triangular shape which has been described as representing a broad "Thuja-tree" during early gestation [31] and a Christmas tree during midgestation [10] and [32]. In contrast, the villous trees of early S. caffer placentomes are best described as a "Tuscany-cypress" in appearance due to their slender form and rudimentary branching, rather resembling villi described in B. bubalis [8] and [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal villi of cattle, measured at the centre of pedunculated placentomes, were up to four times wider than in the African buffalo whereas the width of villous tips was similar in both genera. Villous trees in cattle therefore adopt a triangular shape which has been described as representing a broad "Thuja-tree" during early gestation [31] and a Christmas tree during midgestation [10] and [32]. In contrast, the villous trees of early S. caffer placentomes are best described as a "Tuscany-cypress" in appearance due to their slender form and rudimentary branching, rather resembling villi described in B. bubalis [8] and [27].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the villous trees of early S. caffer placentomes are best described as a "Tuscany-cypress" in appearance due to their slender form and rudimentary branching, rather resembling villi described in B. bubalis [8] and [27]. It has been noted that during late gestation in cattle, tall-conical-shaped villous trees allow a denser arrangement of villi within a single placentome, which results in the maximal functional surface area of villous tissue in a given space [32]. In the African buffalo placenta, the simple yet dense villous arrangement during early gestation may compensate for the distinctly less developed villous branching when compared to that of cattle at similar fetal developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, the placenta grows faster than the foetus in early pregnancy but slower after mid-gestation, when foetal weight surpasses that of the placenta (Eley et al 1978, Prior & Laster 1979, Reynolds et al 1990. Morphologically, the bovine placenta is considered fully developed at mid-to late gestation, but foetal villous trees continue to develop (branching pattern) and rearrange (spatial relationship between endothelium and trophoblast) in placentomes until near term, increasing the villous SA, which will also accommodate foetal demands for growth towards the end of gestation (Leiser et al 1997). However, the placental tissue holds a great plastic capacity in facing unusual, adverse circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Leiser et al (1997) reported that the endocytosis of the fluid Anais da Academia Brasileira de Ciências (2012) 84(4): 1115-1120 (Annals of the Brazilian Academy of Sciences) Printed version ISSN 0001-3765 / Online version ISSN 1678-2690 www.scielo.br/aabc substance (pinocytosis) was structurally evident in the units of apical and basal membranes of all endothelial and epithelial placental barriers.…”
Section: Introductionmentioning
confidence: 99%